Prevalence and family function associated with suicide-related behaviors in vocational college population of southern China: the mediating role of depression - He Wang; Yingyu Zhong; Yueyun Wang (Frontiers in Psychiatry)
BackgroundSuicide is positively associated with a range of psychological risk factors such as family function and depression. However, it remains unclear if depression mediates the association between family function and suicide in Chinese adolescents.MethodsWe enrolled 14263 students from Shenzhen Polytechnic College, China. Family function, depression and suicide were assessed in these students by self-report measures, respectively. With path analysis and logistic regression, the mediating role of depression in the association between family function and suicide was analyzed.ResultsIn this study, the detection rate of suicide-related behaviors among vocational school students was 12.19%, among which the detection rates of suicide idea, suicide plan and suicide attempt were 11.59%, 4.26% and 2.70%, respectively. Depression played a significant mediating role in the influence of family function on suicide-related behaviors.ConclusionsPoor family function might increase the risk of suicide-related behaviors in vocational school students, and this effect was partly realized by affecting their mental health. Improving family function could not only improve adolescent’s psychological status, but also reduce their suicide-related behaviors.